Causal Information Flow in European Financial Markets : Transfer Entropy Analysis of News Sentiment and STOXX50 Returns - Požár, Borek; Sabolovič, Mojmír, 1978-; Dvořák, Jiří; Vysoká škola ekonomická v Praze. Fakulta managementu (2025)
We investigated whether public sentiment conveys information preceding stock returns for the European STOXX50 companies. We collected daily closing prices and news headlines over the last circa 400 trading days via Refinitiv Eikon. We used the FinBERT model for sentiment classification and estimated multivariate transfer entropy employing nonparametric nearest-neighbor estimators, while ensuring significance using hierarchical testing and false-discovery-rate correction. The analysis revealed only one statistically significant information flow, likely representing a chance finding given the number of tests. These results support the semi-strong form of the Efficient Market Hypothesis, where sentiment signals are immediately reflected in prices. We release our code that combines modern sentiment analysis with rigorous, interpretable information-theoretic methods, providing a replicable approach for future studies and practical applications.
Vedoucí práce: Mojmír Sabolovič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses